The evolving field of Dermato‐oncology and the role of dermatologists: Position Paper of the EADO, EADV and Task Forces, EDF, IDS, EBDV–UEMS and EORTC Cutaneous Lymphoma Task Force. (24th August 2020) - Garbe, C.; Peris, K.; Soura, E.; Forsea, A.M.; Hauschild, A.; Arenbergerova, M.; Bylaite, M.; del Marmol, V.; Bataille, V.; Samimi, M.; Gandini, S.; Saiag, P.; et al.
Abstract: Background: The incidence of skin cancers has been increasing steadily over the last decades. Although there have been significant breakthroughs in the management of skin cancers with the introduction of novel diagnostic tools and innovative therapies, skin cancer mortality, morbidity and costs heavily burden the society. Objective: Members of the European Association of Dermato‐Oncology, European Academy of Dermatology and Venereology, International Dermoscopy Society, European Dermatology Forum, European Board of Dermatovenereology of the European Union of Medical Specialists and EORTC Cutaneous Lymphoma Task Force have joined this effort to emphasize the fundamental role that the specialist in Dermatology–Venereology has in the diagnosis and management of different types of skin cancer. We review the role of dermatologists in the prevention, diagnosis, treatment and follow‐up of patients with melanoma, non‐melanoma skin cancers and cutaneous lymphomas, and discuss approaches to optimize their involvement in effectively addressing the current needs and priorities of dermato‐oncology. Discussion: Dermatologists play a crucial role in virtually all aspects of skin cancer management including the implementation of primary and secondary prevention, the formation of standardized pathways of care for patients, the establishment of specialized skin cancer treatment centres, the coordination of an efficient multidisciplinary team and the setting up of specific follow‐up plans for patients. Conclusion: Skin cancers represent an important health issue for modern societies. The role of dermatologists is central to improving patient care and outcomes. In view of the emerging diagnostic methods and treatments for early and advanced skin cancer, and considering the increasingly diverse skills, knowledge and expertise needed for managing this heterogeneous group of diseases, dermato‐oncology should be considered as a specific subspecialty of Dermatology–Venereology.